A LITERATURE REVIEW: FACTORS RELATED TO THE PASUNG AMONG PEOPLE WITH MENTAL ILLNESS: DOI: https://doi.org/10.35654/ijnhs.v2i2.95 - Angelina Roida Eka; Novy Helena Catharina Daulima (International Journal of Nursing and Health Services (IJNHS), 2019)
Physical restraint and confinement (pasung) by families of people with mental illness is known to occur in many parts of the world Pasung is a common human right violation on people with mental illness found on every country in the world especially in developing countries like Indonesia. In Indonesia the term pasung refers to the physical restraint or confinement of "criminals, crazy and dangerously aggressive people. Despite the classification as Human Right Violation, pasung is constantly performed in Indonesia. In 2018, around 18% people with mental ilness experienced pasung. This study aimed to identify factors related to pasung. The researcher conduct the literature review on the credible sources. Five databases were used including Science Direct, Proquest, Scopus, Ebsco, and Google Scholar. Study result identified that factors related to pasung come from person with mental illness, family and community. The pasung phenomena within the community on people with mental illness ironically have a limited sources of research especially the ethnographic study of the said phenomena. Ethnographic study on pasung is important to elucidate the social and cultural meanings of the practice in a variety of settings and cultures especially in Indonesia, which take an enourmous impact within the community including the practice of pasung on people with mental illness.